Damage Evaluation Methods Of Structural Members Using Acoustic Emission (Ae) Technique - Panjsetooni, Alireza (2013)
Acoustic emission (AE) is an important nondestructive evaluation (NDE) technique used in the field of structural engineering for both case local and global monitoring. This technique was employed to investigate the process of fracture formation in reinforced concrete and steel structures. In main objective of this research was damage evaluation assessment of reinforced concrete beam and frame as well as welded steel beam specimen, in order to provide a commercial method for the non-destructive evaluation of reinforced concrete and steel structures.A number of reinforced concrete (RC) one story frames and several RC beam specimens with continuous or non-continuous longitudinal rebar were prepared. In addition, several welded steel beam specimens were fabricated. These specimens were tested under loading cycle and were simultaneously monitored using AE technique. The AE test data was analyzed using the number of AE analysis method such as AE source location, b-value analysis method, and damage parameter, Relaxation ratio, Load ratio, Calm ratio and intensity analysis. The trend of these methods during loading and unloading was compared with behaviour of each type of specimens. The results showed that these methods were able to indicate the levels of damage. Also, the results showed that AE can be considered as a viable method to predict the remaining service life of reinforced concrete and steel structure. In addition, with respects to the results obtained from AE analysis, a number of new charts were proposed.